?????? ??????? ??????? ?? ????? ????? ??????? ???? ???????? ??? - Mabruroh Maburoh (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2017)
Arabic is a language studied in various parts of the world. Learning Arabic is not an easy one, but it takes hard work from various parties, wether from the teacher or students. Especially if the Arabic language learners are not from native speakers, of course this will be a tough challenge for an Arabic teacher. The existence an Arabic language environment will greatly help learning Arabic for non-native speakers, either in their own learning or in improving language skills. The Arabic environment consists of two types, namely the formal Arabic environment and the non-formal Arabic environment. Each of them play a very important role in learning Arabic, inside or outside the classroom, because everything around the student, whether audio or visual, will greatly influence the success of learning Arabic. So, it is very important for researchers to know about what is the Arabic environment and what is the role in helping Arabic learning for non-native speakers.